Feeding management and production factors affecting goat milk composition and quality. I. Titratable acidity and rennetcoagulation - Superchi P.; Summer A.; Sabbioni A.; Malacarne M.; Franceschi P.; Mariani P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Individual milk samples representing the overall morning milking were collected monthly (from April to September) from 24 Saanen goats, uniformly distributed into two herds in Northern Italy, with the aim to evaluate the factors affecting titratable acidity and rennet-coagulation parameters. Herds differed in feeding management system: Traditional and Total Mixed Ration. Delivery date, parity number (primiparous or pluriparous), delivery type (single or twin) were considered. In correspondence of test days, lactation stage and milk yield data were recorded. All milk samples were analysed for fat, protein, lactose, urea, somatic cells, pH, titratable acidity and rennet-coagulation parameters. Herd type significantly affected titratable acidity. Titratable acidity showed a positive relationship with milk yield and protein content and a negative one with pH. Milk from primiparous goats had a higher titratable acidity and a better clotting time. Milk from single delivery goats was characterised by a higher titratable acidity. Lower values of titratable acidity were accompanied by a worsening of curd firming time and curd firmness. Among rennet-coagulation parameters, herd type influenced only curd firming time. An increase of protein content was related to a worse clotting time, a lower k20 and a higher a30. An increase of lactose content was related to an improvement of rennet-coagulation parameters. Curd firming time worsening was related to increased somatic cells and pH; pH was also related to an increase of clotting time.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)